Analisis kualitas air dan limbah pertambangan nikel di Sungai Pesouha, Sulawesi Tenggara - Amelia, Febrina Risky; Effendi, Hefni; Kurniawan, Budi; Andrianto, Charles; Ahmady, Taufik (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
This study aims to assess the water quality of the Pesouha River and identify key pollution-contributing parameters using various types of analysis. The Pollution Index Analysis values range from 0.617 to 2.47, indicating quality from good to light pollution. Additionally, the Water Quality Index (WQI-INA) analysis results range from 79.2 (fairly good) to 90.93 (very good). Correlation analysis of Cr6+ and iron (Fe) in water is 0.91; TSS and (Cr6+) is 0.85; TSS and Fe is 0.86; TSS and IP is 0.68; Cr6+ and IP is 0.72; Fe and IP is 0.6. Regression analysis using hexavalent chromium (Cr6+) as the independent variable (X) and the Pollution Index as the dependent variable (Y) yielded a multiple R-value of 0.722, indicating a strong correlation between X and Y. The Adjusted R2 value is 0.46, meaning X can explain Y, in this case, the parameter (Cr6+) can explain Y or Pollution Indeks by 46%, and other factors influence the rest. The regression equation formed is Y = (-0.099) + (0.12) X, meaning that if the value of X = 0. then the value of Y is (-0.99) with a positive relationship between parameters.